A 4‐Arm Small Molecule Acceptor with High Photovoltaic Performance. (16th August 2022) - Meng, Xianyi; Li, Mingjie; Jin, Ke; Zhang, Lixiu; Sun, Jie; Zhang, Wenhua; Yi, Chenyi; Yang, Junliang; Hao, Feng; Wang, Guan‐Wu; Xiao, Zuo; Ding, Liming
Abstract: Manipulating the backbone of small molecule acceptors (SMAs) is of particular importance in developing efficient organic solar cells (OSCs). The common design is constructing 2‐arm SMAs with linear or curved backbones. Herein, we report an acceptor 4A‐DFIC with a 4‐arm backbone unexpectedly generated in the reaction of an electron‐rich aromatic diamine and hexaketocyclohexane. Single‐crystal X‐ray diffraction analysis indicates the rigid and twisted molecular plane and the effective molecular stacking of 4A‐DFIC in solid state. 4A‐DFIC shows a low band gap of 1.40 eV and excellent light‐harvesting capability from visible to near‐infrared region. Binary and ternary OSCs based on 4A‐DFIC gave power conversion efficiencies (PCEs) of 15.76 % and 18.60 % (certified 18.1 %), respectively, which are the highest PCEs for multi‐arm SMA‐based OSCs to date. Abstract : A 4‐arm small molecule acceptor (SMA) 4A‐DFIC was serendipitously made. Power conversion efficiencies of 15.76 % and 18.60 % were achieved in 4A‐DFIC‐based binary and ternary organic solar cells, respectively, setting new records for multi‐arm SMA‐based solar cells.